Patient Characteristics and Outcomes of Nonmetastatic Breast Cancer in Haiti: Results from a Retrospective Cohort. (13th July 2020) - Fadelu, Temidayo; Damuse, Ruth; Lormil, Joarly; Pecan, Elizabeth; Dubuisson, Cyrille; Pierre, Viergela; Rebbeck, Timothy; Shulman, Lawrence N.
Abstract: Background: There are few studies on breast cancer outcomes in the Caribbean region. This study identified a retrospective cohort of female patients with nonmetastatic breast cancer in Haiti and conducted survival analyses to identify prognostic factors that may affect patient outcomes. Methods: The cohort included 341 patients presenting between June 2012 and December 2016. The primary endpoint was event‐free survival (EFS), defined as time to disease progression, recurrence, or death. Descriptive summaries of patient characteristics and treatments were reported. Survival curves were plotted using Kaplan‐Meier estimation. Multivariate survival analyses were performed using Cox proportional hazards regression. Results: Median age at diagnosis was 49 years, with 64.2% being premenopausal. Most patients (55.1%) were staged as locally advanced. One hundred and sixty patients received neoadjuvant therapy: 33.3% of patients with early stage disease and 61.2% of those with locally advanced stage disease. Curative‐intent surgery was performed in 278 (81.5%) patients, and 225 patients received adjuvant therapy. Adjuvant endocrine therapy was used in 82.0% of patients with estrogen receptor–positive disease. During the follow‐up period, 28 patients died, 77 had disease recurrence, and 10 had progressive disease. EFS rates at 2 years and 3 years were 80.9% and 63.4%, respectively. After controlling for multiple confounders, the locally advanced stage group had a statistically significant adjusted hazard ratio for EFS of 3.27 compared with early stage. Conclusion: Patients with nonmetastatic breast cancer in Haiti have more advanced disease, poorer prognostic factors, and worse outcomes compared with patients in high‐income countries. Despite several limitations, curative treatment is possible in Haiti. Implications for Practice: Patients with breast cancer in Haiti have poor outcomes. Prior studies show that most Haitian patients are diagnosed at later stages. However, there are no rigorous studies describing how late‐stage diagnosis and other prognostic factors affect outcomes in this population. This study presents a detailed analysis of survival outcomes and assessment of prognostic factors in patients with nonmetastatic breast cancer treated in Haiti. In addition to late‐stage diagnosis, other unfavorable prognostic factors identified were young age and estrogen receptor‐negative disease. The study also highlights that the availability of basic breast cancer treatment in Haiti can lead to promising early patient outcomes. Abstract : Disparities in global breast cancer outcomes are well established; however, few studies describe potential contributors to poor outcomes in Haiti and other countries in the Caribbean region. This article assesses patient outcomes and explores predictors of poor outcomes based on a retrospective cohort of patients with nonmetastatic breast cancer seen at a tertiary care facility in Haiti.